2021
DOI: 10.1182/bloodadvances.2021004250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DNMT3A variant allele frequency and double mutation on clinicopathologic features of patients with de novo AML

Abstract: The clinicopathologic features of DNA methyltransferase 3A (DNMT3A)-mutated de novo acute myeloid leukemia (AML), and the significance of variant type, variant allele frequency (VAF), and multiple concomitant DNMT3A mutations, remain poorly defined. We examined 104 DNMT3A-mutated de novo AML patients from 2 major centers. Most (82%) had normal karyotype (NK); R882H variants were frequent(38%). The most commonly comutated genes included nucleophosmin (NPM1; 53%), Fms-related tyrosine kinase 3 (FLT3)–internal ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(39 reference statements)
1
6
1
Order By: Relevance
“…We first investigated the biological and clinical impact of DNMT3A mut VAF on CN‐AML, which be stratified by the cut‐off value of 42%. For biological features, we observed that DNMT3A High patients at diagnosis had a significantly higher WBC counts and a trend for higher BM blast percentage compared with DNMT3A Low ones, further strengthing a previous report by Narayanan et al 38 that that DNMT3A High (≥44%) patients presented with leukocytosis and higher blast counts, and they further demonstrated that DNMT3A VAF had a positive correlations with WBC counts in AML patients. Combining these two data sets suggested that higher WBC counts and BM blast percentage might be unique biological features for patients with CN‐AML with DNMT3A High .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We first investigated the biological and clinical impact of DNMT3A mut VAF on CN‐AML, which be stratified by the cut‐off value of 42%. For biological features, we observed that DNMT3A High patients at diagnosis had a significantly higher WBC counts and a trend for higher BM blast percentage compared with DNMT3A Low ones, further strengthing a previous report by Narayanan et al 38 that that DNMT3A High (≥44%) patients presented with leukocytosis and higher blast counts, and they further demonstrated that DNMT3A VAF had a positive correlations with WBC counts in AML patients. Combining these two data sets suggested that higher WBC counts and BM blast percentage might be unique biological features for patients with CN‐AML with DNMT3A High .…”
Section: Discussionsupporting
confidence: 87%
“…Although the predictive results of DNMT3A VAF are rarely reported, our findings were similar to previous reports. An analysis of 104 patients with DNMT3A ‐mutated AML led by Narayanan et al 38 showed that high DNMT3A VAF was associated with more inferior OS and EFS, but had no impact on CR rate in univariable analyses, but in multivariable analyses, the adverse effect of DNMT3A High only on OS but not on EFS in the CN‐AML subset. Linch et al 39 reported that high DNMT3A R882 mut VAF (≥47%) also presented worse effects on CR rate and OS in univariable analyses, but were not significant in multivariable analyses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, FLT3 mutations are detected in about one-third of AML patients, and these mutations are directly related to the poor prognosis of AML [33]. However, interestingly, the mutation rates of DNMT3A, FLT3, NPM1, and IDH2 were higher in the low CD86 expression group in our study [34,35]. Te mutation rate of RUNX1 was higher in the CD86 group, which could be because of the number of samples.…”
Section: Discussioncontrasting
confidence: 50%
“…The gene is likely mutated in early stages of leukemogenesis, as DNMT3A Mu can be found in non‐leukemic elderly adults, and as a germline mutation in familial AML 1,3,25 . This suggests the need for further cooperating mutations such as NPM1 Mu , FLT3 Mu , IDH1 Mu , IDH2 Mu , and TET2 Mu to develop overt AML (co‐mutated in 53%, 25%, 23%, 23%, and 21% of AML, respectively) 26 . DNMT3A Mu is mutually exclusive of favorable cytogenetic markers in AML such as t ( 15;17 ) and CBF‐AML 9 .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the need for further cooperating mutations such as NPM1 Mu , FLT3 Mu , IDH1 Mu , IDH2 Mu , and TET2 Mu to develop overt AML (co-mutated in 53%, 25%, 23%, 23%, and 21% of AML, respectively) 26. DNMT3A Mu is mutually exclusive of favorable cytogenetic markers in AML such as t(15;17) and CBF-AML 9.…”
mentioning
confidence: 99%